The Effect of Moringa oleifera Leaf Extract on Theca Cell in Polycystic Ovary Syndrome Model with Insulin Resistance - Wulandari, L P; Hapsari, A (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Polycystic ovary syndrome (PCOS) is known as the commonest endocrine disorder in women of reproductive age and often associated with insulin resistance, hyperandrogenemia, chronic inflammation, and oxidative stress. The use of Moringa oleifera as an antioxidant should be investigated as an alternative treatment of follicular refinement in PCOS with insulin resistance. We aimed to prove the effect of Moringa oleifera leaf extract in various dosages to decrease the theca cell thickness of PCOS female rat with insulin resistance. This study was a laboratory experimental research. Three month old Rattus norvegicus stran Wistar rat weighing 100- 130 grams were divided into 5 groups (n = 8). PCOS model obtained by giving injection of testosterone propionate for 28 days, followed by metformin therapy and Moringa oleifera leaf extract at 250 and 500 mg/KgBW for 14 days. Then, we analyzed the thickness of theca cell. Statistical analysis used One Way Anova that was performed with IBM SPSS Statistics versions 24.00. The examination of ovarium histology showed that leaf extract Moringa oleifera 500 mg/KgBW (0.931±0.457) significantly decreased the thickness of theca cells (p <0.05) compared to the PCOS control group. The conclusions was Moringa oleifera leaf extract as an antioxidant proven to decrease the thickness of theca cell of the female rat model of PCOS